The impact of creativity and PKWU learning achievement on entrepreneurial interest among high school students - Sadiyah, Allimatus; Setyawan, Aris Budi (Communications in Humanities and Social Sciences, 2025)
This study investigates the influence of creativity and Prakarya dan Kewirausahaan (PKWU) learning achievement on entrepreneurial interest among high school students in Indonesia, where youth unemployment remains high despite curriculum reforms aimed at fostering entrepreneurship. Using Structural Equation Modeling (SEM), data were analyzed from 235 grade 12 students at a Depok high school through validated questionnaires and academic records. Results revealed that both creativity and PKWU learning achievement significantly and positively influence entrepreneurial interest, with PKWU learning achievement demonstrating a substantially stronger impact (β = 0.567, p < 0.001) compared to creativity (β = 0.311, p = 0.005). These findings indicate that while creativity contributes meaningfully to entrepreneurial aspirations, practical entrepreneurship education through PKWU has a more direct and substantial effect on students' career interests. The study concludes that educational institutions should prioritize integrating hands-on entrepreneurial experiences alongside creativitydevelopment to effectively cultivate entrepreneurial mindsets. The results provide evidence for strengthening practical components in entrepreneurship curricula and suggest that structured business skills training may be more influential than general creative development in fostering student interest in entrepreneurship as a viable career path.